2020
DOI: 10.1002/acn3.51157
|View full text |Cite
|
Sign up to set email alerts
|

Software‐based analysis of 1‐hour Holter ECG to select for prolonged ECG monitoring after stroke

Abstract: Objective: Identification of ischemic stroke patients at high risk for paroxysmal atrial fibrillation (pAF) during 72 hours Holter ECG might be useful to individualize the allocation of prolonged ECG monitoring times, currently not routinely applied in clinical practice. Methods: In a prospective multicenter study, the first analysable hour of raw ECG data from prolonged 72 hours Holter ECG monitoring in 1031 patients with acute ischemic stroke/TIA presenting in sinus rhythm was classified by an automated soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The 24 hours traditional Holter and 2 hours single-lead Holter tests are both electrocardiogram (ECG) monitoring tests that are used to diagnose arrhythmias; however, few studies have investigated the differences in accuracy and diagnostic efficiency between these two methods. 21 This study compared the aforementioned issues with a 24 h- improvements in the following aspects: (i) making the acquisition process more convenient and less intrusive. (ii) leads to the wider adoption of arrhythmia screening in primary healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 24 hours traditional Holter and 2 hours single-lead Holter tests are both electrocardiogram (ECG) monitoring tests that are used to diagnose arrhythmias; however, few studies have investigated the differences in accuracy and diagnostic efficiency between these two methods. 21 This study compared the aforementioned issues with a 24 h- improvements in the following aspects: (i) making the acquisition process more convenient and less intrusive. (ii) leads to the wider adoption of arrhythmia screening in primary healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our research also found that ECG was ambiguous in the PSVC/PVC diagnosis and burden analysis (data not shown). The 24 hours traditional Holter and 2 hours single‐lead Holter tests are both electrocardiogram (ECG) monitoring tests that are used to diagnose arrhythmias; however, few studies have investigated the differences in accuracy and diagnostic efficiency between these two methods 21 . This study compared the aforementioned issues with a 24 h‐Holter and a 2 h‐Holter among patients requiring PSVC/PVC monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation